ИССЛЕДОВАНИЕ СИСТЕМЫ ГЕНЕРИРОВАНИЯ ПЕРЕМЕННОЙ ЧАСТОТЫ ПОСТОЯННОЙ АМПЛИТУДЫ НА БАЗЕ МАГНИТОЭЛЕКТРИЧЕСКОГО ГЕНЕРАТОРА И ПОЛУПРОВОДНИКОВОГО ПРЕОБРАЗОВАТЕЛЯ - Макаров, Д.В.; Харитонов, С.А.; Юхнин , М.М. (Інститут електродинаміки НАН України, Київ, 2012)
Electromagnetic processes in the power generating system of variable current and variable frequency based on permanent magnet synchronous machine and semiconductor converter carried out reactive load to influence equivalent flux linkage of generator on are studied. Relations to basic parameters of converter and generator be calculated are investigated. The work is carried out under the State contract No. 13.G36.31.0010 dated as of October 22, 2010. References 3, figures 2.